Reduksi Harmonik dengan Common Mode pada Inverter 500 Watt - Muhirno, Muhirno; Setiawan, Agus; Irwansyah, Nurkahfi (EPIC Journal of Electrical Power Instrumentation and Control, 2024)
In order not to be disconnected from the electrical energy source, a backup system is needed. One way is to use a charging system when PLN is on and storing it in an accumulator for use during a PLN blackout. However, when charging, the electricity stored in the accumulator is in the form of DC current, so it needs to be converted back to AC current, namely with an AC to DC inverter. The inverter system uses switching which creates harmonics. Disturbances in the electric power system caused by wave and current distortion are called harmonics. Harmonics can cause sinusoidal waves to become less sinusoidal, caused by high frequency waves which are multiples of the fundamental frequency. To reduce harmonics, install an EMI filter at the inverter output. This research measures the effectiveness of installing a filter using Labview 2014 software on a 500 W custom low inverter with inductive, resistive and capacitive loads using Labview software and the NI myDAQ instrument. The results of the research are that the standby/no-load power required for the common mode EMI filter is 0.03 A’s at a voltage of 220VAC. In no-load conditions there was an increase in THDv of 0.03 from before the filter 1.7% to 1.739%, and a decrease in THDi of 0.12 from 1.311% to 1.119%. In conditions with inductive loads, there was a decrease in THDv by 0.104 from before the filter 1.202% to 1.098%, and THDi by 0.099% from before the filter 1.325% to 1.226%. In conditions with resistive loads, there was a decrease in THDv of 0.12 from before the filter of 1.218% to 1.09%, and THDi of 0.003 from before the filter of 1.144% to 1.114%. In conditions with capacitive load, there was an increase in THDv of 0.185 from before the filter of 1.219% to 1.404% and a decrease in THDi of 0.035 from before the filter of 1.44% to 1.109%.